A systematic review of prenatally diagnosed vein of Galen malformations: prenatal predictive markers and management from fetal life to childhood - Di Meglio, Lavinia; Sica, Giordana; Toscano, Paolo; Orlandi, Giuliana; Manzo, Luigi; Mazzarelli, Laura Letizia; Sica, Carmine; Di Meglio, Aniello (Frontiers in Pediatrics, 2024)
Introduction: Vein of Galen malformations (VGMs)account for less than 1% of all intracranial vascular malformations. However, in the fetal and pediatric populations, they represent the most common vascular malformation of the brain. An optimal knowledge of the prenatal and postnatal clinical features is mandatory for effective management. Methods: Articles published between 1st January 2003 and 31st January 2024, reported in PUBMED and EMBASE, were evaluated for a systematic review analyzing prenatal and postnatal features and management of fetal Galean VGMs. Results: Thirty-one papers reporting information on 51 prenatally-diagnosed VGM were included. The most common prenatal features were: fetal hydrocephalus (39%) and cardiomegaly (56%). Post-natal data of 43 VGM cases are described. The overall mortality was 58,14%. 77,78 % of the survivors had a normal development. Conclusions: A close follow-up and a multidisciplinary approach is mandatory to manage this condition. Our study aimed to provide a guide to gynecologists, neonatologists, cardiologists, and neuroradiologists.